A GAP analysis of the current state of Pain Management Services in the UK, 2024 - Sue Copley; Beatrice Bretherton; Suzanne Carty; Matthew Brown; Sailesh Mishra; Emmy Kato Clarke; Ganesan Baranidharan; Devjit Srivastava (BJA Open)
Background: In the UK, multidisciplinary services for patients experiencing chronic pain are currently commissioned by the NHS as specialised services. Pain services across the UK were placed under significant strain during the COVID pandemic. The ‘GAP Analysis working group’ (GAP group) was commissioned by the Board of the Faculty of Pain Medicine (FPM) in November 2021 to evaluate the post-COVID state of pain services across the country. Methods: The GAP group's remit was to establish any deficit in pain services when measured against the service ‘gold standard’ outlined in the published FPM document ‘Core Standards for Pain Management Services volume 2.0’ (CSPMS). A survey was developed using an iterative consensus process among the group and was distributed to all FPM members. Results: The survey included questions pertaining to 21 standards. There were 164 respondents to this GAP analysis from 97 individual clinical sites delivering pain services in the UK. The majority of respondents worked in secondary care (74%), followed by tertiary care (23%) and finally primary care (3%). No single standard was met by all reporting sites. The degree of compliance with individual standards varied, ranging from only 30% of sites reporting full compliance (standard 9: research and development) to 79% of sites reporting full compliance (standard 21: interventional pain procedure). Conclusions: The following aspects of chronic pain services need urgent redress: provision of paediatric pain services, provision of cancer pain services, outcome data management support, research and development, and increased support of psychological services and pain management programme access.